Landscape architecture: a study about representation and memory case study: squares in Pelotas - 1860-1930 - Mattos, Maria Regina de (Paisagem e Ambiente, 2007)
The analysis of the urban space concept that these areas embody, this study aims to understand the complex relationship between people and nature e established in these spaces. This investigation is to study the public urban areas that are represented by the squares locateds in the centralarea of the city of Pelotas (1860 and 1930). At that time, the economic prosperity provoked a significant urban growth, together with the spatial organization of the buildings and the streets helped to influence thefinal shape of the areas, and de consequent appropriation of these squares by the users.